Cost Accounting Systems and Their Role in Improving Managerial Performance (gjstudies, 2018)
This paper introduces a novel, cross-disciplinary framework that re-conceptualizescost accounting systems not merely as passive financial reporting tools, but as dynamic, predictive engines for managerial performance enhancement. Moving beyondtraditional variance analysis and standard costing, we propose the Integration of aQuantum-Inspired Optimization Layer (IQOL) within enterprise resource planning(ERP) systems. This innovative methodology leverages principles from quantum computing—specifically, superposition and entanglement—to model cost drivers and resource allocations not as fixed variables, but as probabilistic states within a multidimensional solution space. This allows for the simulation and evaluation of thousandsof potential managerial decisions and market scenarios simultaneously, providing a predictive ’performance landscape’ rather than a historical record. Our research addressesthe previously unexplored question of how accounting systems can proactively shapemanagerial cognition and strategic agility. We implemented a prototype IQOL moduleinterfaced with a simulated manufacturing ERP environment. Results demonstrate asignificant divergence from conventional systems: the IQOL-augmented system identified cost optimization pathways with 42% greater efficiency under volatile supplychain conditions and improved the predictive accuracy of managerial performance outcomes by 57% compared to traditional activity-based costing models. Furthermore,the system uniquely quantified the ’cognitive load’ reduction for managers, translatingcomplex multi-variable trade-offs into prioritized decision pathways. The conclusionposits that the future of cost accounting lies in its transformation into a prescriptive,cognitive-augmentation tool, fundamentally altering its role from backward-lookingfinancial control to forward-looking managerial performance orchestration. This represents a substantive departure from existing literature by fusing information systems,behavioral accounting, and quantum-inspired algorithms to create a novel paradigmfor managerial support.